Windows Admin Center - Rodrick, Mike; Goodwin, Sophia (Packt Publishing, 2024)
Dive into the comprehensive world of Windows Admin Center, a modern and efficient management tool designed to streamline IT administration tasks. This video series starts with an overview of Windows Admin Center, explaining its significance and integration with other management tools. You'll learn the installation and configuration process for various operating systems, including Windows 10 and Windows Server. The series then explores advanced configurations, including user roles, access permissions, and effective access control. You'll also cover the installation and use of extensions to expand Windows Admin Center's functionality. Practical insights into preparing your environment, adding and managing nodes, and overseeing Windows Servers and Windows 10 PCs are provided. In the final section, you'll connect your on-premises environment to Azure, learning how to deploy and manage Azure VMs directly from Windows Admin Center. By the end of this series, you'll have a solid foundation in using Windows Admin Center to manage diverse environments, streamlining IT operations and enhancing administrative capabilities.
Online resource; title from title details screen (O'Reilly, viewed August 5, 2024)
Keywords: Microsoft Windows server; Operating systems (Computers); Systèmes d'exploitation (Ordinateurs); operating systems; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet